Aerial plant biomass and litterfall as local determinants of leaf litter and fine root decomposition in a semiarid ecosystem of the Neotropical region. Issue 4 (2nd October 2019) - Oliveira, Uirandé; Megali Amado, André; Vasconcellos, Alexandre
Abstract: The rate of litter decomposition can vary within ecosystems that have high spatial heterogeneity, and many uncertainties remain regarding the abiotic and biotic factors that act as determinants of decomposition rates at small spatial scales. This study investigated the decomposition rates of leaves and fine roots of Croton sonderianus Mull. Arg., Poincianella pyramidalis Tul., and Aspidosperma pyrifolium Mart. over 12 months in a semiarid ecosystem in Brazil. Twelve biotic and abiotic factors were also evaluated as local determinants of decomposition rates. A 2000 × 500 m grid was delimited within which thirty 20 × 20 m plots were established. Two sets of litterbags were installed in each plot, one containing a mixture of leaves and the other a mixture of roots. The approximate mean lost mass was 90% for leaf material and 47% for roots after 10 and 12 months, respectively. Due to the litterbag incubation sites being distributed in a heterogeneous area, values for the intrinsic decay coefficient ( k) (through month) varied widely from a minimum of 0.073 to a maximum of 0.458 for leaf litter and from 0.045 to 0.077 for roots. Variation in the decay coefficients for leaves and roots was significantly explained by aerial plant biomass and litterfall production, respectively; more open areas exhibited the highest rates of decomposition. Vegetation structure that favors the exposure of soil to solar radiation can influence the decomposition process, promoting an increase in leaf, and fine root decomposition rates at small spatial scales in tropical semiarid ecosystems.